Intrinsic motivation in open source software development - Jürgen Bitzer; Wolfram Schrettl; Philipp J. H. Schröder (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2004)
This papers sheds light on the puzzling evidence that even though open source software (OSS) is a public good, it is developed for free by highly qualified, young and motivated individuals, and evolves at a rapid pace. We show that once OSS development is understood as the private provision of a public good, these features emerge quite naturally. We adapt a dynamic private-provision-of-public-goods model to reflect key aspects of the OSS phenomenon. In particular, instead of relying on extrinsic motives for programmers (e.g. signaling) the present model is driven by intrinsic motives of OSS programmers, such as user-programmers, play value or homo ludens payoff, and gift culture benefits. Such intrinsic motives feature extensively in the wider OSS literature and contribute new insights to the economic analysis.
Keywords: L86; H41; L31; 330; open source software; public goods; homo ludens; war of attrition